Implementation of Cooperation Agreement Between Widya Mataram University and Bahana Batik in Copyright Protection of Widya Mataram University Batik Design - Zaki Sierrad, Muhammad; Rusmala Ratnawati, Erna Tri; Rifka Novita Maharani Armawati (Fakultas Hukum Universitas Widya Mataram, 2022)
Batik is a fabric that has enormous differences from other kinds of fabric in design and manufacturing aspects. The Batik design is a masterpiece, created in the form of image design with unique characteristics, which has a copyright that is bounded to be protected by the law. This study focused on the copyright protection of Batik design. The purpose of this study is to learn the implementation of an agreement between Widya Mataram University and Bahana Batik as well as to find out the legal protection of batik design copyright in the cooperation agreement. This research uses the empirical research method with a juridical approach which is conducted by collecting data from interviews and by studying the agreement document which is further analyzed qualitatively. The results showed that the agreement was done under the hands and regulated the rights and obligations in the uniform procurement agreement. However, the agreement only regulates the prohibition for the use of the Widya Mataram Logo and does not include copyright ownership of batik design, thus the copyright of the batik design remains owned by Bahana Batik in accordance with Article 36 of undang-undang No. 28 of 2014 about Copyright. Key Words : Batik, Copyright, Cooperation Agreement